Pediatric Shoulder Girdle - Farooq, Mobeen; Belair, Jeffrey A.; Desai, Vishal (Seminars in Musculoskeletal Radiology, 2024)
The pediatric shoulder girdle is a complex anatomical structure uniting the upper extremity and trunk. The osseous structures, their articulations, and the surrounding soft tissue support structures (muscles, tendons, and ligaments) allow for a wide range of motion at the shoulder. Growth and maturation of the components at the shoulder girdle vary, particularly the osseous structures. This characteristic renders interpretation of imaging of the pediatric shoulder girdle more challenging because normal or variant anatomy can be confused for pathology. We review the physiologic growth and maturation of the shoulder girdle with special emphasis on the development of the bones and their articulations. The role of various imaging modalities and the common osseous and soft tissue variants in the pediatric shoulder are also discussed.
Keywords: pediatric radiology; shoulder girdle; ossification centers; normal maturation; variant anatomy